An empirical, model, or virtual author? - Paweł Bohuszewicz; Tomasz Szymon Markiewka (Przestrzenie Teorii, 2014)
The article titled Autor: empiryczny, modelowy czy wirtualny? [“An empirical, model, or virtual author?”] presents a discussion about the terms used in the title which was held by the article’s authors. P. Bohuszewicz defends the validity of the concepts of an empirical and a virtual author, the latter being the result of “rewriting” Umberto Eco’s idea of a model author. T. Szymon Markiewka claims that the concept of a model author and that of a virtual author are unnecessary multiplications of theoretical entities: we only need the concept of an empirical author, but we also need to remember about all the complications related to this concept.